2014
DOI: 10.1016/j.ijrobp.2014.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalated Liver Stereotactic Body Radiation Therapy at the Mean Respiratory Position

Abstract: Purpose The dosimetric impact of dose-probability based PTV margins for liver cancer patients receiving SBRT was compared to standard PTV based on the internal target volume (ITV). Plan robustness was evaluated by accumulating the treatment dose to ensure delivery of the intended plan. Methods and Materials Twenty patients planned on exhale CT for 27–50 Gy in 6 fractions using an ITV-based PTV and treated free-breathing were retrospectively evaluated. Iso-toxic, dose-escalated plans were created on mid-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…These results of sufficient target coverage and a significant reduction of the PTV are in agreement with the use of a midV approach for the liver (15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results of sufficient target coverage and a significant reduction of the PTV are in agreement with the use of a midV approach for the liver (15).…”
Section: Discussionsupporting
confidence: 86%
“…However, the penumbra in the abdominal region is known to be narrower (13,14), which could partly depreciate the added value of using the midV concept instead of an ITV. It has been shown that for liver tumors, the midV approach ensured sufficient target coverage, and a mean PTV reduction of 38% was reported (15). However, no information on dose to the surrounding OARs was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that for patients with less than 8 mm of anterior abdominal motion, the T0, T50, or average phases of the 4D CT produced acceptable target coverage over the 10 phases of the 4D CT (2,11). This data provides initial evidence that using planning techniques for bolus design, smearing parameters, blocks, and modulation wheel selection as described by Moyers et al (10) are sufficient to accommodate for WPL changes due to respiration for tumors of the pancreas.…”
Section: Discussionsupporting
confidence: 57%
“…Our results show that for patients with less than 8 mm of anterior abdominal motion, the T0, T50, or average phases of the 4D CT produced acceptable target coverage over the 10 phases of the 4D CT (2,11). This data provides initial evidence that using planning techniques for bolus design, smearing parameters, blocks, and modulation wheel selection as described by Moyers et al (10) are sufficient to accommodate for WPL changes due to respiration for tumors of the pancreas.…”
Section: Discussionmentioning
confidence: 78%